A MULTIMODAL DISCOURSE ANALYSIS OF E-ADVERTISEMENT VISUALS - SYEDA ZAHIDA RIZVI; NAYAB WAQAS KHAN; MAHWISH FAROOQ (International Journal of Psychosocial Rehabilitation, 2026)
This research tends to investigate the persuasive and attractive modes used in an e-advertisement visual by the advertisers to persuade and affect the buyers or viewers. As the study deals with semiotic modes along with language in a visual, to that end, the Multimodal Discourse Analysis of Kress & Leeuven, (1996) is employed as a framework for analyzing the collected data. Three Meta functions will help in interpreting three meanings, i.e., representational, interactional and compositional given through different elements of the selected visuals and meaning of each element which in some way influences the others in the context. The data for the research includes six e-advertisement visuals, taken from different online shopping sites through random sampling. The data was analyzed like semiotic resources, focus on the font, capitalization, boldness etc. in detail. The findings will help the consumers to have an insight about the advertisement tactics adopted by the advertisers.